Responses of Blue Tits (Cyanistes caeruleus) and Great Tits (Parus major) to con- and hetero-specifics alarm calls - Romero, Mónica (Jihočeská univerzita, 2021)
I conducted analyses of the responses of Blue Tits and Great Tits to familiar and unfamiliar Titmice species using playbacks of alarm calls of Blue Tit, Willow Tit, Black-capped Chickadee and Varied Tit at the winter feeder in Branišovský forest, near České Budějovice.
Responses of Blue Tits (Cyanistes caeruleus) and Great Tits (Parus major) to con- and hetero-specifics alarm calls
Keywords: Birds; Titmice; behaviour; playbacks; alarm call; Blue tit; Great tit; Willow tit; Black-capped chickadee; Varied tit; Birds; Titmice; behaviour; playbacks; alarm call; Blue tit; Great tit; Willow tit; Black-capped chickadee; Varied tit